Proteomic analysis and brain-specific systems biology in a rodent model of penetrating ballistic-like brain injury - Boutté, Angela M.; Yao, Changping; Kobeissy, Firas; May Lu, Xi-Chun; Zhang, Zhiqun; Wang, Kevin K.; Schmid, Kara; Tortella, Frank C.; Dave, Jitendra R. (Electrophoresis, 2012)
Proteomics and systems biology have significantly contributed to biomarker discovery in the field of brain injury. This study utilized 2D‐DIGE‐PMF‐MS as a preliminary screen to detect biomarkers in a rat model of penetrating ballistic‐like brain injury (PBBI). Brain‐specific systems biology analysis of brain tissue identified 386 proteins having a fold change of more than 2, of which 321 proteins were increased and 65 were decreased 24 h after PBBI compared to sham controls. The majority of upregulated proteins were cytoskeletal (10.5%), nucleic acid binding (9.3%), or kinases (8.9%). Most proteins were involved in protein metabolism (22.7%), signal transduction (20.4%), and development (9.6%). Pathway analysis indicated that these proteins were involved in neurite outgrowth and cell differentiation. Semiquantitative Western blotting of 6, 24, 48, and 72 h after PBBI indicated ubiquitin carboxyl‐terminal hydrolase isozyme L1 (a proposed traumatic brain injury biomarker in human clinical trials), tyrosine hydroxylase, and syntaxin‐6 were found to be consistently elevated in brain tissue and cerebral spinal fluid after PBBI compared to sham controls. Combining proteomics and brain‐specific systems biology can define underlying mechanisms of traumatic brain injury and provide valuable information in biomarker discovery that, in turn, may lead to novel therapeutic targets.